Patients with metastatic renal cell carcinoma treated with cabozantinib in the Czech Republic: analysis of four cancer centers - Richter, Igor; Poprach, Alexandr; Zemankova, Anezka; Buchler, Tomas; Bartos, Jiri; Samal, Vladimir; Studentova, Hana; Rozsypalova, Aneta; Dvorak, Josef; Brom, Ondrej; Melichar, Bohuslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
AIM: The aim of this study was to retrospectively analyze treatment outcomes and tolerance in patients in whom cabozantinib was used after previous targeted therapy. PATIENTS AND METHODS: Cabozantinib was administered in dose 60 mg/day, a subset of patients received initial dose of 40 mg/day. The treatment was administered until to progression or unacceptable toxicity. CT scans were assessed according to the RECIST 1.1 and toxicity of treatment was assessed based on the CTCAE (version 4). Kaplan-Meier analysis was used to calculate progression free survival (PFS) and overall survival (OS). We performed a multivariate analysis of risk factors for treatment outcomes (PFS, OS) by Cox regression analysis. All statistics were evaluated at the significance level alpha = 0.05. RESULTS: 54 patients with metastatic renal cell carcinoma (mRCC) were evaluated. Median PFS in all patients treated with cabozantinib was 9.3 months (95% CI 5.3 - 13.3). One-year survival was 85.2% (95% CI 72.9 - 93.4%). Treatment response was observed in 45.9% of cases, including one complete remission. Cox regression analysis demonstrated that presence of subsequent treatment was the only factor with a significant effect on OS (P=0.008). Adverse events occurred in 88.9% of patients, grade 3 - 4 in 46.3%. CONCLUSION: The analysis of our cohort of patients treated with cabozantinib in the second or higher lines of treatment showed that cabozantinib represents an effective and safe therapy and contributes to longer survival of our mRCC patients.
Keywords: nádory ledvin; Humans; Anilides; výsledek terapie; lidé; metastases; toxicity; Pyridines; renal cell carcinoma; cabozantinib; Retrospective Studies; Treatment Outcome; Czech Republic; pyridiny; karcinom z renálních buněk; Carcinoma, Renal Cell; retrospektivní studie; Česká republika; Kidney Neoplasms; anilidy